Concurrent Adrenal Adenoma, Unilateral Adrenal Hyperplasia, and Bilateral Renal Artery Stenosis in a 61-Year-Old Man - Sanda Mrabet; Achraf Jaziri; Dorsaf Zellama; Abdellatif Achour; Yosra Hasni; Hamza Elfekih; Ibtissem Hasni Bouraoui; Mohamed Amine Chaari (American Journal of Men's Health)
We report a case of a very rare association of adrenal adenoma, unilateral adrenal hyperplasia, and bilateral renal artery stenosis. A 61-year-old man with a remarkable history of two severe strokes was admitted to the Nephrology department with hypertension associated with severe hypokalemia and metabolic alkalosis. Doppler of renal arteries was not conclusive, so contrast-enhanced scanning was done revealing a left adrenal adenoma, right adrenal hyperplasia, and bilateral moderate renal artery stenosis. After control of blood pressure with central anti-hypertensive drugs and calcium channel blockers and normalization of kalemia under potassium supplementation, the hormonal analysis was done showing an elevated plasma aldosterone concentration at 1,568 pmol/L, with a direct renin concentration below the detection level. Primary aldosteronism was confirmed and the prescription of an anti-aldosterone agent led to the control of blood pressure and potassium plasmatic levels. In front of arterial hypertension with hypokalemia, we recommend the assessment of secondary and primary hyperaldosteronism in a systematic way since the association of two or even three etiologies of hyperaldosteronism is possible and an appropriate diagnosis is essential for adequate treatment.